PESANTREN DAN PENGEMBANGAN TRADISI ISLAM-KEBANGSAAN - Wahyu Choerul Cahyadi (IBDA` : Jurnal Kajian Islam dan Budaya, 2011)
This article describes a discourse and a Islamic- nation culturaldevelopment in pesan Trend Ilmu Giri Yogyakarta community. The datais gained by observation, interview and documentation. The subject ofthis research are the Islamic scholars and the congregation. The data isanalyzed using sociological and pedagogic approach. This article showsthat the congregation are encouraged to see, listen, and feel somethingdifferent from their culture. This is an important media to create a newmind-set to accommodate the differences in an Islamic - nation frame.